Biochemical basis of vocal fold mobilization after microflap surgery in a rabbit model. (9th July 2013) - Mitchell, Joshua R.; Kojima, Tsuyoshi; Wu, Hongmei; Garrett, C. Gaelyn; Rousseau, Bernard
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To investigate phonation‐related extracellular matrix (ECM) changes in the vocal fold lamina propria after microflap surgery using an in vivo rabbit phonation model. Study Design Prospective animal study. Methods Twenty‐four New Zealand White rabbits were used in this study. Quantitative polymerase chain reaction and immunohistochemistry were used to investigate alterations in vocal fold ECM proinflammatory and profibrotic gene, and protein expression from a control group of animals receiving a microflap without phonation and a separate group of animals receiving experimentally induced phonation on postmicroflap days 0, 3, and 7. Results IHC demonstrated the highest concentration of CD45 in vocal folds on postoperative day 0. Staining for CD45 was absent by postoperative day 7, with no differences in CD45 staining between groups. Fibronectin gene expression increased significantly on postoperative day 3 in the control and experimentally induced phonation groups, with maximal staining of fibronectin around the microflap incision on postoperative day 7. No alterations in cyclooxygenase‐2, interleukin‐1β, and transforming growth factor‐β1 gene expression were observed between groups. Conclusions Results of the present study revealed an acute inflammatory response in the vocal fold at the time of microflap (day 0) and up to 3 days post‐microflap. By post‐operative day 3, staining of CD45 positive cells decreased, with essentially no evidence of inflammation by post‐operative day 7. With the end of the acute inflammatory response occurring around day 3, these data may provide support for mobilizing tissue after inflammation has subsided and the process of active tissue remodeling has ensued (days 3–7). Level of Evidence N/A. Laryngoscope, 124:487–493, 2014